General investigation memorandum, Susitna Hydroelectric Project, aquatic program, fiscal year 1984. (Document (Susitna Hydroelectric Project), 1983)
This general investigation memorandum sets forth the objectives, methodology, organization, personnel, schedule, deliverables, and budget for accomplishing the fisheries and aquatic habitat studies needed to support the Federal Energy Regulatory Commission licensing of the Susitna Hydroelectric Project. The activities and budget described in this memorandum are for fiscal year 1984 (July 1983 through June 1984).